Determining Factors in The Interest of Using QRIS (A Case Study of MSMEs in Karanganyar Regency): Faktor-Faktor Yang Menentukan Minat Penggunaan QRIS (Studi Kasus UMKM Di Kabupaten Karanganyar) - Khasanah, Dina Uswatun; Arfiansyah, Mufti Arief (Universitas Muhammadiyah Sidoarjo, 2025)
MSMEs or Micro, Small and Medium Enterprises have a vital role in maintaining the stability of the Indonesian economy. MSMEs as one of the merchant users of QRIS are required to continue to be creative and adapt to increasingly advanced technological advances. This study aims to examine the relationship between interest in utilizing QRIS among MSME actors in Karanganyar Regency with factors of convenience, perceived benefits, security, and knowledge. The data used consists of primary data, specifically collected through distributing questionnaires and conducting interviews with MSME owners. The research population was 95 respondents using the purposive sampling method. The analysis method in solving the problems studied and testing the hypothesis is multiple regression analysis. The data processing process uses SPSS software version 26. The research findings state that the variables of perceived benefits & knowledge have an influence on interest in using QRIS and convenience & security have no influence on the dependent variable.